Scientific Opinion on the re‐evaluation of Brown HT (E 155) as a food additive - EFSA Panel on Food Additives and Nutrient Sources (ANS) (EFSA Journal, 2010)
Abstract The Panel on Food Additives and Nutrient Sources added to Food provides a scientific opinion re‐evaluating the safety of Brown HT (E 155). Brown HT has been previously evaluated by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) in 1977 and 1984 and the EU Scientific Committee for Food (SCF) in 1975 and 1984. JECFA established an Acceptable Daily Intake (ADI) of 0‐1.5 mg/kg body weight (bw)/day, while the SCF established an ADI of 0–3 mg/kg bw/day. The Panel was not provided with a newly submitted dossier and based its evaluation on previous evaluations, additional literature that became available since then and the data available following a public call for data. The Panel concluded that based on a long‐term carcinogenicity and toxicity study in mice an ADI of 1.5 mg/kg bw/day can be derived. The Panel concludes that at both the maximum permitted level of use (Tier 2) and at the maximum reported levels of use of Brown HT (Tier 3), mean intake estimates are generally below the ADI of 1.5 mg/kg bw/day. However, in both adults and 1–10 years old children, the high percentile of exposure for both Tiers can be higher than the ADI at the upper end of the range.